Globalization and Health Inequities in Latin America (Springer International Publishing, 2018)
This book critically analyses the influence of international policies and guidelines on the performance of interventions aimed at reducing health inequities in Latin America, with special emphasis on health promotion and health in all policies strategies. While the implementation of these interventions plays a key role in strengthening these countries' capacity to respond to current and future challenges, the urgency and pressures of cooperation and funding agencies to show results consistent with their own agendas not only hampers this goal, but also makes the territory invisible, hiding the real problems faced by most Latin American countries, diminishing the richness of local knowledge production, and hindering the development of relevant proposals that consider the territory's conditions and cultural identity. Departing from this general analysis, the authors search for answers to the following questions: Why, despite the importance of the theoretical advances r egarding actions to address social and health inequities, haven't Latin American countries been able to produce the expected results? Why do successful initiatives only take place within the framework of pilot projects? Why does the ideology of health promotion and health in all policies mainly permeate structures of the health sector, but not other sectors? Why are intersectoral actions conjunctural initiatives, which often fail to evolve into permanent practices? Based on an extensive literature review, case studies, personal experiences, and interviews with key informants in the region, Globalization and Health Inequities in Latin America presents a strategy that uses monitoring and evaluation practices for enhancing the capacity of Latin American and other low and middle-income countries to implement sustainable processes to foster inclusiveness, equity, social justice and human rights. &nb sp;.